Control of mango anthracnose using plant tonic - Daten Mustafa, Nurul Izzati (2017)
Anthracnose is a disease which is one of the major problem that reduce world mango production (Yahia, 2011). It is a postharvest disease that cause because of the high rainfall and high humidity that promote infestation of mycelium of fungus C. gloeosporioides (Fitzell and Peak, 1984; Jeffries et al., 1990; Dodd et al., 1992). Black lesion of the disease make the fruit is in bad appearance and reduce its taste. This is serious can be control physically, chemically and biologically. Nowadays, demand for biological approach being elevated since people now more aware about food production localize from natural alternatives . This is study will be conducted to identify plant tonic as a biological approach to control anthracnose on mango. Plant extract or Plant Tonic will be used to suppress C. gloeosporioides. This method is still new but there is evidence that it will be effective to control anthracnose. Therefore, this study were conducted to evaluate more about potential of Plant Tonic as a biocontrol surfactant to control anthracnose. Plant Tonic made up of natural ingredients that contain some of free fatty acid such as lauric acid, caprylic acid, acpric acid or myristic acid that helps to against pathogen by a few regulations. Result from this study is mango was free from black lesion of anthracnose after treat with plant tonic. This were indicate that black lesion of anthracnose were suppressed as a result of suppression by plant tonic that have ability to inhibit the growth of C. gloeosporioides on the mango.